Sequence analysis of the COL5A2 gene in patients with spontaneous cervical artery dissections - Grond-Ginsbach, Caspar; Wigger, Frank; Morcher, Marion; Pein, Florian von; Grau, Armin J.; Haußer-Siller, Ingrid; Brandt, Tobias (Neurology, 2002)
The authors searched for mutations in the gene that codes for the α2 chain of type V procollagen in 10 patients with spontaneous cervical artery dissections (sCAD). Two patients carried a missense mutation affecting the predicted C-propeptide (T1227S; D1429V). A third patient carried two mutations (V509A and P830L) in the same α2(V) chain. The T1227S mutation and the V509A/P830L haplotype also were detected among 50 healthy subjects. The D1429V substitution was detected neither in a series of 150 healthy control subjects nor among 50 additional patients with sCAD.